The Andes Cordillera. Part III: glacier surface mass balance and contribution to sea level rise (1979–2014). (20th October 2016) - Mernild, Sebastian H.; Liston, Glen E.; Hiemstra, Christopher; Wilson, Ryan
ABSTRACT: Glacier surface mass balance (SMB) observations for the Andes Cordillera are limited and therefore estimates of the SMB contribution to sea‐level rise are highly uncertain. Here (in Part 3), we simulate glacier surface meteorological and hydrological conditions and trends for the Andes Cordillera (1979/80–2013/14; 35 years), covering the tropical latitudes in the north down to the sub‐polar latitudes in the far south, including the Northern Patagonia Icefield (NPI) and Southern Patagonia Icefield (SPI). Surface meteorological conditions and heat‐ and mass‐transfer processes were simulated for all glaciers having an area equal to or greater than 0.5 km 2 . SnowModel – a fully integrated energy balance, blowing‐snow distribution, multi‐layer snowpack, and runoff routing model – was used to simulate glacier SMBs for the Andes Cordillera. The Randolph Glacier Inventory (RGI; v. 4.0) and NASA Modern‐Era Retrospective Analysis for Research and Applications (MERRA) products, downscaled in SnowModel, allowed us to conduct relatively high‐resolution (1‐km horizontal grid; 3‐h time step) simulations of glacier air temperature, precipitation, sublimation, evaporation, runoff, and SMB. These simulated glacier SMBs were verified against both independent direct observed annual glacier SMB and satellite gravimetry and altimetry derived SMB, indicating a good agreement. For Andes glaciers, the 35‐year mean annual SMB was found to be −1.13 m water equivalent (w.e.), while the cumulative SMB was −39.6 m w.e., which is equal to a cumulative SMB contribution of 3.4 mm sea‐level equivalent (SLE) (∼0.1 mm SLE per year). However, for both NPI and SPI, the mean SMB was positive (where likely calving explains why geodetic estimates are negative). For the Andes Cordillera, the simulated mean glacier‐specific runoff was 41 L s −1 km −2, while for NPI and SPI it was 213 and 198 L s −1 km −2, respectively, indicating available water resources from NPI and SPI.